History curriculum, nation-building and the promotion of common values in Africa: A comparative analysis of Zimbabwe and South Africa (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
A challenge for Africa is how to derive common values from the values of diverse communities. The challenge becomes even more difficult in the face of notions such as autonomy, multiculturalism and respect for difference which are accompanying the emergence of neo-liberalism, globalisation and cosmopolitanism. While it is important to respect diversity in a postcolonial society, it is equally important that nation-building should strive for the promotion of common values among the citizenry. This article uses the example of Zimbabwe and South Africa as a comparative case study to investigate how the ruling elites in these two southern African countries have endeavoured to apply the curriculum for nation-building and the promotion of common citizenship by inculcating common values in young citizens. The article also explores the role of the curriculum from the perspective of social constructivism, where ‘curriculum’ is defined as an agency to foster social, cultural and political ideals in society. The academic discipline that is highly vulnerable to the imperatives of nation-building and the interests of the political elite is history, as it is prone to manipulation by political regimes in their hegemonic projects.
Keywords: Nation-building; Curriculum; Multi-culturalism; Hegemony; History; Ideology